Role of organizational environment in sustained organizational economic performance. Issue 1 (1st November 2021) - Baloch, Qadar Bakhsh; Maher, Sourath; Iqbal, Nadeem; Shah, Syed Naseeb; Sheeraz, Muhammad; Raheem, Faryal; Khan, Kanwal Iqbal
Abstract : Purpose: Therefore, this research study investigates the impact of business environment on the performance of the business organizations. (1) To understand the importance the environment in the success of the business entrepreneurship. (2) To explore the environmental factors that can affect the success of business entrepreneurship in Pakistan. (3) To establish relationship between the environmental factors and the sustained organizational performance of business entrepreneurships in Pakistan. Design/methodology/approach: Drawing from the person–environment fit (PE fit) and the self-determination theory literature, this survey research study seeks to determine the impact of organizational environment upon sustained organizational economic performance. The main independent variable of the study encompasses its main three dimensions, i.e. leadership capacity, organizational culture and organizational politics. The dependent variable comprises the sustained economic performance of the organization. The research study hypothesized and tested a model in which the organizational environment (organizational culture, organizational politics and leadership) interplays with the organizational sustained performance. Findings: Keeping in view the outcomes of this research work the following implications can be drawn. A leader can yield maximum productivity of employees, if he/she has leadership capacity to provide directions, skilled to minimize the stress level of the employees and able to motivate them in achieving organizational goals. Therefore, capacity of leader to handle difficult situations and develop PE fit is the key to organizational success in current scenario. The study also revealed a positive effect of organizational culture on organizational performance. The culture of the organizations provides an environment of openness to think, share and contribute toward goals of the organization. It enables employees to express themselves, develop person-organization common goals with self-determination. The PE fit provides a platform to feel free, express their feelings and opinions, and contribute in the decision-making process of organizations. The involvement in organizational activities provide a sense of responsibility, ownership and motivation to produce better results for the organizations. Originality/value: PE fit perspective postulates that matching individual psychological needs and environmental supplies (provided by organization and society) generates positive attitudes and behaviors (Tepper et al., 2018). The effect between individuals and their environment is inherently reciprocal rather than a one-way effect (Goetz et al., 2021). The fundamental postulation support that the fit certainly improves performance, commitment and satisfaction of individuals in the context of organizations (De Cooman et al., 2019; Rau vola et al., 2020). Moreover, self-determination theory (SDT) is another perspective that emphasizes the attainment of autonomy, competence and relatedness in employees to outperform (Deci and Ryan, (2010). The self-determination theory revolves around the social-contextual conditions that support or obstruct the integral courses of self-motivation and psychological development, which will contribute toward organizational performance (Nazir et al., 2021).